Ablação ocular no camarão Macrobrachium rosenbergii (De Man) (Crustacea, Decapoda, Palaemonidae): efeitos sobre a reprodução, pigmentação epidérmica e atividade alimentar - Santos, Marcel José Martins dos [UNESP]; Pinheiro, Marcelo Antônio Amaro [UNESP] (Sociedade Brasileira de Zoologia, 2000)
This study analyze the consequences of unilateral and bilateral ablation based on ovigerous percentage, consecutive spawns, and secondary effects of the surgical process in the females of Macrobrachium rosenbergii (De Man, 1879). Two experiments were carried out with four and seven months old females in intermolt stage. Each experiment was comprised of control, unilateral and bilateral ablation. Eyestalk ablation was done with a bistoury with a topic hot cauterization followed by application of antibiotic pomades. The animals were maintained at constant temperature (28 ± 1,05ºC) and photoperiod of 12L: 12D within fibercement boxes with sandy bottom and biological filter. Females were observed once a day during fourteen weeks, registering gonadal condition, ecdysis and presence of spermatophore (mating) and spawning. Unilateral ablation technique is more efficient due to the anticipation of the first spawn, repeatability between spawns, expressive rate of ovigerous females and survival, that favored its applicability. Bilateral eyestalk ablation produced the mortality of ali the females with change in coloration and food activity patterns. These results corroborate other observations on penaeid shrimps. though bilateral ablation on some lobsters was a success. These results showing an interespecific variation and can be used in aquaculture projects.
Eyestalk ablation in the prawn Macrobrachium rosenbergii (De Man) (Crustacea, Decapoda, Palaemonidae): effects on reproduction, epidermic pigmentation and feeding activity
Keywords: Crustacea; eyestalk ablation; reproduction; pigmentation; feeding activity; prawn